The Economics of the Modern Construction Firm - Gruneberg, Stephen L.; Ive, Graham J. (Palgrave Macmillan UK, 2000)
This is a book about the whole diverse range of firms that are found in the construction sector, about their decision-making and the economic environments in which they operate. The authors aim to provide a new and coherent perspective on these firms and the choices they have to make - both for their managers and for all who have a stake in these firms and their industry. This book offers some new and important perspectives for research and teaching about construction firms